2017
DOI: 10.24912/jm.v20i3.15
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Ukuran Dewan, Kepemilikan Saham Oleh Direktur, Dan Jender Terhadap Kinerja Keuangan Perbankan

Abstract: Abstrak: Tujuan penelitian ini adalah untuk mengetahui apakah mekanisme tata kelola perusahaan, khususnya ukuran dewan direktur, kepemilikan saham oleh direktur, dan jender, berpengaruh terhadap kinerja keuangan perbankan di Indonesia. Pada penelitian ini, kami menggunakan sampel 16 bank (45 observasi) yang terdaftar di bursa efek Indonesia antara tahun 2011 dan 2014. Metode analisis yang digunakan ialah regresi fixed effects dan random effects. Dikontrol oleh variabel ukuran perusahaan, hutang, dan pertumbuha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 35 publications
(61 reference statements)
1
3
0
5
Order By: Relevance
“…The results of this study are supported by Anggraeni et al (2014), Mardiyati and Murdayanti (2016), Rafinda et al (2018), andArulvel andPratheepkanth (2019) which suggests that gender diversity has no effect on the firm performance. This is due to the existence of a minority female board of directors so that female board members do not have significant skills to provide knowledge such as prestige, legitimacy, skills and connections to external resources (Anggraeni et al, 2016).…”
Section: The Effect Of Gender Diversity On Firm Performancesupporting
confidence: 81%
See 2 more Smart Citations
“…The results of this study are supported by Anggraeni et al (2014), Mardiyati and Murdayanti (2016), Rafinda et al (2018), andArulvel andPratheepkanth (2019) which suggests that gender diversity has no effect on the firm performance. This is due to the existence of a minority female board of directors so that female board members do not have significant skills to provide knowledge such as prestige, legitimacy, skills and connections to external resources (Anggraeni et al, 2016).…”
Section: The Effect Of Gender Diversity On Firm Performancesupporting
confidence: 81%
“…The study found that the gender diversity of the board of directors in consumer goods industry companies had a negative and insignificant impact on the firm performance. The existence of a female board of directors in the firm is ineffective in improving the firm performance (Mardiyati & Murdayanti, 2016).…”
Section: The Effect Of Gender Diversity On Firm Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Dalam penelitian ini dewan direksi diproksikan dengan kepemilikan saham dewan direksi yang mana semakin tinggi tingkat kepemilikan dari dewan direksi maka direksi akan memiliki motivasi tinggi untuk meningkatkan kinerja dalam perusahaan. Hal ini juga menandakan bahwa antara pihak manajemen dan pemegang saham dapat meminimalisir munculnya konflik keagenan dikarenakan pihak manajemen akan mengusahakan untuk meningkatkan kinerja bagi kesejahteraan pemegang saham termasuk dirinya (Mardiyati & Murdayanti, 2017) (Musallam, 2020). Hal bertentangan (Fadillah, 2017) yang menyatakan bahwa semakin tinggi kepemilikan saham manajerial dapat menurunkan kinerja perusahaan.…”
Section: Tinjauan Literatur Dan Perumusan Hipotesisunclassified
“…Good corporate governance will affect the reputation of a company where a good reputation then it will have an impact on the interest of investors to invest their shares. According to Mardiyati and Murdayanti (2016), better corporate governance will get better company performance too.…”
Section: Introductionmentioning
confidence: 99%